Health care of sexual and gender minorities: an integrative literature review - Jedison Feliciano Silva; Gabriela Maria Cavalcanti Costa
ABSTRACT Objectives: to describe health care practices aimed at lesbians, gays, bisexuals, transvestites, and transsexuals. Methods: an integrative literature review based on systematic steps, in MEDLINE, LILACS AND SciELO databases and/or electronic libraries. It was held from September to November 2018, with articles published between 2012 and 2017, available in full in Portuguese, English, and Spanish, addressing health care to that population group. Results: fourteen articles were included. Most of the articles were about the trajectory of individuals within health services and showed limitations and obstacles in the use of these services. Final Considerations: there is evidence that factors related to organization of services, attitude of professionals, stigma, and discrimination experienced undermine health care practices. Therefore, it is essential to carry out educational activities in health services and educational institutions.